2013
DOI: 10.1371/journal.pone.0076707
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Blue Light and Caffeine Effects on Cognitive Function and Alertness in Humans

Abstract: The alerting effects of both caffeine and short wavelength (blue) light have been consistently reported. The ability of blue light to enhance alertness and cognitive function via non-image forming neuropathways have been suggested as a non-pharmacological countermeasure for drowsiness across a range of occupational settings. Here we compare and contrast the alerting and psychomotor effects of 240 mg of caffeine and a 1-h dose of ~40 lx blue light in a non-athletic population. Twenty-one healthy subjects perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 47 publications
4
44
1
1
Order By: Relevance
“…As already suggested [4,7,16,21], the Yerkes-Dodson law [17] would explain how the arousing effects of light could lead to different results depending on the initial state of the individual. For example, under very low levels of basal arousal, light could be ineffective, but this effect can be restored by caffeine administration [19].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…As already suggested [4,7,16,21], the Yerkes-Dodson law [17] would explain how the arousing effects of light could lead to different results depending on the initial state of the individual. For example, under very low levels of basal arousal, light could be ineffective, but this effect can be restored by caffeine administration [19].…”
Section: Discussionmentioning
confidence: 97%
“…This finding makes sense in the context of research suggesting that arousal mediates acute effects of light. Indeed, studies reporting differential sensitivity to light exposure probably involved manipulations in basal arousal, for example, due to presentation of novel stimuli, sleep deprivation, adverse circadian phase, mental fatigue, caffeine intake or demanding tasks [4,13,15,16,1821,39]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mills, Tomkins, and Schlangen [17] found significantly less fatigue and daytime sleepiness, improved alertness and work performance, greater vitality and better mental health in a shift-working call center with high correlated color temperature (17000 K) fluorescent lights with greater blue light wavelengths that can stimulate ipRGCs. There is a growing body of evidence that blue light can improve mood, alertness, memory, cognitive performance and aids in coping with any effect of a post-lunch dip on the EEG and in performance [18][19][20][21][22][23]. Hedge and Nou [24] found that electrochromic glass also may improve worker visual comfort and satisfaction, and reduce symptoms associated with CVS.…”
Section: Introductionmentioning
confidence: 99%
“…It was particularly important to assess sleep in this study, as recent reports suggest that computer screen-generated light in the blue range can impact human health via several related pathways and in multiple organs (Tosini et al 2016;Kayaba et al 2014;Beaven and Ekstrom 2013) or may have no effect (O'Hagan et al 2016). For example, one study showed that the blue light of LED-backlit computer screens significantly suppressed melatonin production in human subjects (Sroykham and Wongsawat 2013).…”
Section: Conclusion and Discussionmentioning
confidence: 99%